A Study to Evaluate the Cause of Bone Demineralization in Gynecological Cancer Survivors. (30th January 2013) - Stavraka, Chara; Maclaran, Kate; Gabra, Hani; Agarwal, Roshan; Ghaem‐Maghami, Sadaf; Taylor, Alexandra; Dhillo, Waljit S.; Panay, Nick; Blagden, Sarah P.
Abstract : Learning Objectives: Describe the potential contributors to bone demineralization in patients receiving systematic treatment for gynecological malignancies. Define what is meant by "osteopenia" and "osteoporosis" and describe their relevance to fracture risk. Explain the importance of preventing and managing bone mineral loss and its complications in gynecological cancer survivors. Background: An association between treatment for gynecological cancers and risk of osteoporosis has never been formally evaluated. Women treated for these cancers are now living longer than ever before, and prevention of treatment‐induced morbidities is important. We aimed to distinguish, in gynecological cancer survivors, whether cancer therapy has additional detrimental effects on bone health above those attributable to hormone withdrawal. Methods: We performed a retrospective cross‐sectional analysis of dual energy x‐ray absorptiometry (DEXA) scan results from 105 women; 64 had undergone bilateral salpingo‐oophorectomy (BSO) followed by chemotherapy or radiotherapy for gynecological malignancies, and 41 age‐matched women had undergone BSO for benign etiologies. All were premenopausal prior to surgery. Results: The median age at DEXA scan for the cancer group was 42 years, and 66% had received hormonal replacement therapy (HRT) following their cancer treatment. For the benign group, the median age was 40 years, and 87% had received HRT. Thirty‐nine percent of cancer survivors had abnormal DEXA scan results compared to 15% of the control group, with the majority demonstrating osteopenia. The mean lumbar spine and femoral neck bone mineral densities (BMDs) were significantly lower in cancer patients. A history of gynecological cancer treatment was associated with significantly lower BMD in a multivariate logistic regression. Conclusions: Women treated for gynecological malignancies with surgery and adjuvant chemotherapy have significantly lower BMDs than age‐matched women who have undergone oophorectomy for noncancer indications. Prospective evaluation of BMD in gynecological cancer patients is recommended to facilitate interventions that will reduce the risk of subsequent fragility fractures. Abstract : The prevalence of low bone mineral density in premenopausal women treated for gynecological cancer is explored and the direct effect of cancer treatment versus that of hormone withdrawal on the bone health of gynecological cancer survivors is evaluated.